2007
DOI: 10.1038/nri2036
|View full text |Cite
|
Sign up to set email alerts
|

PI3Kδ and PI3Kγ: partners in crime in inflammation in rheumatoid arthritis and beyond?

Abstract: Dysregulated signal transduction in innate and adaptive immune cells is known to be associated with the development of various autoimmune and inflammatory diseases. Consequently, targeting intracellular signalling of the pro-inflammatory cytokine network heralds hope for the next generation of anti-inflammatory drugs. Phosphoinositide 3-kinases (PI3Ks) generate lipid-based second messengers that control an array of intracellular signalling pathways that are known to have important roles in leukocytes. In light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
357
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(365 citation statements)
references
References 125 publications
6
357
0
2
Order By: Relevance
“…The results confirmed that 9AA treatment results in downregulation of p110g levels. In addition, whereas p110g expression Small molecule targeting AKT/mTOR, PI3K, NF-jB and p53 pathways C Guo et al was previously shown to be limited to cells of hematological origin (Camps et al, 2005;Rommel et al, 2007), we found that p110g is expressed in tumor cell lines of various origins, including RCC, fibrosarcoma (HT1080), colon carcinoma (HCT116). We tested different 9AA doses and lengths of treatment and observed downregulation of p110g expression as early as 4-8 h after treatment with at least 5 mM 9AA (Figure 1 and data not shown).…”
Section: P110g Expression Is Decreased In Tumor Cells Treated With 9aamentioning
confidence: 57%
“…The results confirmed that 9AA treatment results in downregulation of p110g levels. In addition, whereas p110g expression Small molecule targeting AKT/mTOR, PI3K, NF-jB and p53 pathways C Guo et al was previously shown to be limited to cells of hematological origin (Camps et al, 2005;Rommel et al, 2007), we found that p110g is expressed in tumor cell lines of various origins, including RCC, fibrosarcoma (HT1080), colon carcinoma (HCT116). We tested different 9AA doses and lengths of treatment and observed downregulation of p110g expression as early as 4-8 h after treatment with at least 5 mM 9AA (Figure 1 and data not shown).…”
Section: P110g Expression Is Decreased In Tumor Cells Treated With 9aamentioning
confidence: 57%
“…In the current study, a 2 ARmediated signaling induced PI3K activation and rapid endocytosis in DCs, and blocking PI3K activation inhibited NAmediated endocytosis. PI3Ks are divided into class I, class II, and class III, based on their structural similarities (31,32). Class I PI3Ks control many cellular functions, including growth, proliferation, survival, adhesion, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that both airway eosinophilia and remodeling were reduced in phosphoinositide 3 kinase γ (PI3Kγ)-deficient mice challenged with OVA (27). Because PI3Kγ is known to be expressed particularly in leukocytes (28) and is known to be activated by G protein-coupled chemokine receptors to induce leukocyte migration (28), it was suggested that chemokines such as eotaxin play key roles in not only airway eosinophilia but also airway remodeling. Whether the infiltrated eosinophils are involved in remodeling should be further examined under the condition in which eosinophilia completely disappeared.…”
Section: Effects Of Anti-il-5 Mab On the Development Of Airway Remodementioning
confidence: 99%